Passively Q-switched thulium-doped fiber laser with silver-nanoparticle film as the saturable absorber for operation at 2.0 μm - Ahmad, Harith; Samion, M.Z.; Muhamad, A.; Sharbirin, A.S.; Ismail, Mohammad Faizal (John Wiley & Sons, 2016)
In this work, a compact thulium-doped fiber laser with a Q-switched output is proposed and demonstrated. A thulium-doped fiber is used for the laser, with a peak absorption of 200 dB m-1 at 790 nm and a cutoff wavelength of 1350 nm as the primary gain medium, and a silver-based saturable absorber as the pulse generation mechanism. The pulses obtained from the proposed laser have repetition rates from 38.3 kHz up to 56.2 kHz, with a pulse width as low as 4.2 μs and pulse energy as high as 67.3 nJ at a maximum pump power of 228.8 mW. The generated pulses are highly stable, showing no changes or fluctuations over operation for a period of 60 min, and further validated with signal-to-noise ratios of 57.0 dB and 59.5 dB in the optical and frequency domains respectively. The proposed laser has high potential for eye-safe applications in manufacturing and medicine.